Islamic professional madrasa teachers and motivation for continuous development: a phenomenological approach - Tambak, Syahraini; Sukenti, Desi (Journal of Education and Learning (EduLearn), 2025)
Many research has been done on professional madrasa (Islamic school) teachers, but incorporating Islamic values and motivation for continuous professional development into them has been neglected. This study aims to determine Islamic professional madrasa teachers based on motivation for continuous professional development in the teaching for future profession. This study used a phenomenological research design, and involving 16 aliyah madrasa teachers as informans. Data was collected by conducting interviews with madrasa teachers and analyzed using a systematic design. This research shows that Islamic professional madrasa teachers are related to prophetic abilities based on Islamic values, moral, and related to human functions as khalifah (leader), imarat al-ard (manage the world), and ‘abdullah (servant who worships Allah). Madrasa teachers view the motivation for future professional involvement in professional Islamic teachers as involvement in self-development through continuous learning, trying to be the best in every activity and fighting endlessly in educating students, anyone who has sincere intentions and has the desire for continuous learning and self-development both academically and non-academicly, training or workshops and also seminars and includes involvement in various forums for future professional development. Teaching is an inseparable part of getting blessings from God (Allah SWT). Utilizing technology to develop learning materials, learning methods, learning evaluation, and others that support the competency of madrasa teachers. Self-improvement has role models that are emulated and practiced in learning.